Synthesis of Chitosan Magnetic Nanoparticles using Glutaraldehyde and Tripolyphosphate as Crosslinker - Rahmani, Indri Alidha; Mulyasuryani, Ani; Andayani, Ulfa (Chemistry Department, The University of Brawijaya, 2022)
Chitosan is an abundant natural polymer, which able to adsorb Pb2+. However, chitosan has the drawback of being unstable in acid and alkaline conditions, so it needs cross-linking. In this article, we will compare the usage of two crosslinkers, glutaraldehyde (GD) and tripolyphosphate (TPP), to solve these issues. The synthesis of chitosan magnetic nanoparticles was carried out by co-precipitation with the addition of glutaraldehyde under acidic conditions and the addition of TPP under alkaline conditions. The results showed that the FTIR spectrum gave characteristic bands at 3131.96 cm-1 (OH and NH), 1635.86 cm-1 (C=O), 1401.97 cm-1 (CN), 1110 cm-1 (COC), and 617 cm-1 (Fe-O). SEM analysis showed that the surface morphology of CMNP-GD particle aggregation was clear more than that of CMNP-TPP. The size of the synthesized nanoparticles was determined by PSA analysis, which was 131.95 Âµm and 137.10 Âµm, respectively. The results of the XRD analysis showed that, in addition to the Fe3O4 and chitosan phases, the produced CMNP also contained Î³-Fe2O3 phase, which was considered to be caused by Fe3O4 oxidation.Â Keywords: nanoparticle, chitosan, magnetic, glutaraldehyde, tripolyphosphate